1996
DOI: 10.1152/ajpcell.1996.271.5.c1438
|View full text |Cite
|
Sign up to set email alerts
|

Contraction-induced injury to single fiber segments from fast and slow muscles of rats by single stretches

Abstract: Susceptibility to contraction-induced injury was investigated in single permeabilized muscle fiber segments from fast extensor digitorum longus and slow soleus muscles of rats. We tested the hypotheses that, after single stretches of varying strains and under three conditions of Ca2+ activation (none, submaximum, and maximum), 1) the magnitude of the deficit in maximum isometric force is dependent on the work done to stretch the fiber, and 2) for each condition of activation and strain, fast fibers incur great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
144
3
6

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(167 citation statements)
references
References 24 publications
14
144
3
6
Order By: Relevance
“…This will increase the series compliance of the muscle, leading to a shift of the angle-force curve to the right . Work on animal muscle fibres by Macpherson et al (1996) has provided electron micrographs which support this hypothesis by Fig. 1 Angle-force curves reconstructed using the fitted quadratic polynomial parameters for each day for the ISO and ECC groups.…”
Section: Discussionmentioning
confidence: 81%
“…This will increase the series compliance of the muscle, leading to a shift of the angle-force curve to the right . Work on animal muscle fibres by Macpherson et al (1996) has provided electron micrographs which support this hypothesis by Fig. 1 Angle-force curves reconstructed using the fitted quadratic polynomial parameters for each day for the ISO and ECC groups.…”
Section: Discussionmentioning
confidence: 81%
“…Note that force and length calibrations are the same across all panels but that the time scale is compressed in b or predictor variables. These predictors were chosen because they have been shown in a previous work to be correlated with eccentric damage (Macpherson et al 1996) or because we had previously shown that they described post-eccentric force of skinned fibers of younger subjects (Choi and Widrick 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Following the physiological measurements, each fiber segment was recovered for electrophoretic analysis. This allowed us to differentiate responses of muscle cells based upon their myosin heavy chain (MHC) isoform expression, an important consideration as muscle cells isolated from faster muscles of adult laboratory rodents appear be more sensitive to injury at the level of the myofilament lattice than fibers isolated from slower muscles (Warren et al 1994;Macpherson et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Single permeabilized LVP muscle fibers were obtained from congenitally-clefted palates of goats before and after surgical repair. The testing of permeabilized fibers allowed for the analysis of the behavior of sarcomeres by eliminating the effects associated with the intact plasma membrane (Macpherson et al, 1996). The hypothesis tested was that repair decreases the percentage of type 2 fibers and the susceptibility to injury to levels that are less than those for nonrepaired cleft palates.…”
Section: Abstract Levator Veli Palatini; Velopharyngeal Incompetencementioning
confidence: 99%
“…The mean cross-sectional area was used to estimate the overall fiber cross-sectional area (CSA). Muscle mass was estimated as the product of L f , CSA, and the density of 1 mg/mm 3 (Macpherson et al, 1996). …”
mentioning
confidence: 99%